Hubungan antara Dukungan Keluarga dengan Mekanisme Koping Perawat Ruang Covid-19 di RSUD Prof. Dr. Margono Soekarjo pada Masa Pandemi Covid-19 - Hapsari, Anindia Firna; Rahayu, Eva; Kusumawardani, Lita Heni (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
Nurses are one of the health workers at the forefront of Covid-19 services are very vulnerable to receiving the impact of the emergence of Covid-19. The effect is a psychological problem that is stress. The individual's way of dealing with stress and adapting to change are performing coping mechanisms. Family support is possible to influence nurses coping mechanisms at work during the Covid-19 pandemic. Find out the relationship between family support and the coping mechanism of the Covid-19 room nurse at Prof. Dr. Margono Soekarjo during the Covid-19 pandemic. This study used a retrospective cohort design. The study was carried out in January 2022 on Covid-19 room nurses at Prof. Hospital. Dr. Margono Soekarjo many 130 respondents using univariate analysis and bivariate analysis of the Spearman test. The results showed that the family support received by respondents was in the excellent category was 124 people (95.4%). Most nurses performed coping mechanisms in the adaptive category many 128 people (98.5%). Bivariate analysis showed p value = 0.005 and r value 0.246. There is a significant relationship between family support and the coping mechanism of the Covid-19 room nurse at Prof. Hospital. Dr. Margono Soekarjo with weak relationship strength.